1996
DOI: 10.1128/aem.62.4.1448-1451.1996
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxypropionaldehyde, an inhibitory metabolite of glycerol fermentation to 1,3-propanediol by enterobacterial species

Abstract: Glycerol fermentation by Enterobacter agglomerans revealed that both growth and 1,3-propanediol production ceased after consumption of about 430 mM glycerol, irrespective of the initial glycerol content. This phenomenon was assigned to the production of 3-hydroxypropionaldehyde, which was identified by proton nuclear magnetic resonance and which showed a bacteriostatic effect. The accumulation during glycerol fermentation was also observed with two other enterobacterial species, i.e., Klebsiella pneumoniae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(61 citation statements)
references
References 9 publications
5
55
0
1
Order By: Relevance
“…The accumulation of 1,3-propanediol, a typical product of glycerol fermentation not found in anaerobic conversions of other organic substrates (Biebl et al, 1999), showed that glycerol was metabolized via the reuterin pathway. Although it is believed that some strains of L. reuteri are unique among propanediol producers in their ability to accumulate reuterin from glycerol (Casas & Dobrogosz, 2000), few enterobacteria and C. butyricum can accumulate reuterin during in vitro fermentation of glycerol (Barbirato et al, 1996;Gonzalez-Pajuelo et al, 2005). These data suggest that small amounts of reuterin were produced in R1 during addition of glycerol by intestinal propanediol-producers such as C. butyricum or commensal L. reuteri, because small concentrations of L. reuteri were detected in fermentation samples from R1.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of 1,3-propanediol, a typical product of glycerol fermentation not found in anaerobic conversions of other organic substrates (Biebl et al, 1999), showed that glycerol was metabolized via the reuterin pathway. Although it is believed that some strains of L. reuteri are unique among propanediol producers in their ability to accumulate reuterin from glycerol (Casas & Dobrogosz, 2000), few enterobacteria and C. butyricum can accumulate reuterin during in vitro fermentation of glycerol (Barbirato et al, 1996;Gonzalez-Pajuelo et al, 2005). These data suggest that small amounts of reuterin were produced in R1 during addition of glycerol by intestinal propanediol-producers such as C. butyricum or commensal L. reuteri, because small concentrations of L. reuteri were detected in fermentation samples from R1.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the findings of Boenigk et al (1993) and Abbad-Andaloussi et al (1996) for 1,3-PD formation in C. freundii and C. butyricum, respectively. It has been argued that the physiological meaning of this limiting step is to avoid the accumulation of 3hydroxypropionaldehyde (3-HPA), which was found to be very toxic to the growth of another 1,3-PD-producing microorganism Enterobacter agglomerans (Barbirato et al, 1996). More experimental investigations are needed to address the possible accumulation of 3-HPA in other 1,3-PDproducing strains.…”
Section: In Vitro and In Vivo Enzyme Activities Under Steady Statesmentioning
confidence: 99%
“…Specific environmental conditions that led to dominance of one fermentation pathway over another (i.e., propionic and isovaleric acid accumulation vs. lactic and formic acid accumulation) appear to have been a determining factor affecting perchlorate biodegradation. Accumulation of inhibitory glycerin fermentation products, such as 3-hydroxylpropionaldehyde, may have also occurred (Barbirato et al, 1996).…”
Section: Resultsmentioning
confidence: 99%